Alterations of Retinal Vasculature in Cystathionine-Beta-Synthase Mutant Mice, a Model of Hyperhomocysteinemia - Tawfik, Amany (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. Mice with moderate/severe hyperhomocysteinemia due to deficiency or absence of the cbs gene encoding cystathionine-beta-synthase (CBS) have marked retinal disruption, ganglion cell loss, optic nerve mitochondrial dysfunction, and ERG defects; those with mild hyperhomocysteinemia have delayed retinal morphological/functional phenotype. Excess homocysteine is a risk factor for cardiovascular diseases; however, it is not known whether excess homocysteine alters retinal vasculature. METHODS. Cbs(+/+), cbs(+/−), and cbs(−/−) mice (age ∼3 weeks) were subjected to angiography; retinas were harvested for cryosections, flat-mount preparations, or trypsin digestion and subjected to immunofluorescence microscopy to visualize vessels using isolectin-B4, to detect angiogenesis using anti-VEGF and anti-endoglin (anti-CD105) and activated glial cells (anti-glial fibrillary acidic protein [anti-GFAP]) and to investigate the blood–retinal barrier using the tight junction markers zonula occludens-1 (ZO-1) and occludin. Expression of vegf was determined by quantitative RT-PCR (qRT-PCR) and immunoblotting. Human retinal endothelial cells (HRECs) were treated with excess homocysteine to analyze permeability. RESULTS. Angiography revealed vascular leakage in cbs(−/−) mice; immunohistochemical analysis demonstrated vascular patterns consistent with ischemia; isolectin-B4 labeling revealed a capillary-free zone centrally and new vessels with capillary tufts midperipherally. This was associated with increased vegf mRNA and protein, CD105, and GFAP in cbs(−/−) retinas concomitant with a marked decrease in ZO-1 and occludin. Homocysteine-treated HRECs showed increased permeability. CONCLUSIONS. Severe elevation of homocysteine in cbs(−/−) mutant mice is accompanied by alterations in retinal vasculature (ischemia, neovascularization, and incompetent blood–retinal barrier). The marked disruption of retinal structure and decreased visual function reported in cbs(−/−) mice may reflect vasculopathy as well as neuropathy.